Comparison of two health related quality of life questionaires in Malay children with strabismus and their parent proxy - Jin Poi, Tan (2015)
Introduction: Strabismus is an eye condition associated with cosmetic, functional and psychosocial circumstances. Evaluation of Health Related Quality of Life (HRQoL) is increasingly recognized as an important factor in strabismus management and a crucial tool for clinical research. However, there are not many strabismus-specific HRQoL assessment tools, especially for children and to our knowledge, no Malay translation for strabismus specific questionnaires. The English versions of IXTQ and AS-20 questionnaires were translated into Malay language and achieved linguistic validation in our study in a hope to apply the questionnaires into our clinical practice. This study also compared the newly developed Malay version of IXTQ and AS-20 HRQoL questionnaires in Malay children with strabismus and their parent proxy. Objective: To compare two health related quality of life (HRQoL) questionnaires for functional and psychosocial aspects in Malay children with strabismus and their parent proxy. Methodology: The questionnaires were translated forward and backward before they were administered to 30 Malay children with strabismus and their parents to determine the internal consistency reliability. The test for Cronbach’s alpha was performed. This was then followed by a comparative cross sectional study conducted in Ophthalmology Clinic and Ward, Hospital Universiti Sains Malaysia from June 2012 until June 2014. A total of 57 Malay children aged 5 to 17 years and their parents were recruited for this study. The children and their parents were then asked to complete the translated Malay version of IXTQ and the AS-20 questionnaires. Children and their parents were given simple verbal and written instructions by a trained personnel and asked to base their responses on their experiences over the previous month. Questionnaires consist of 5 point Likert type scale answer. The total mean scores, functional subscale scores and psychosocial scores were calculated and compared between both questionnaires. Result: The evaluation of the internal consistency for all our newly translated Malay version questionnaires except for Child IXTQ exceeded an alpha of 0.90. The alpha value was 0.909 for Child AS-20, 0.912 for Proxy IXTQ, 0.948 for Proxy AS-20 and 0.651 for Child IXTQ. There was a significant difference noted in the total mean scores and the functional subscale mean scores between both IXTQ and AS-20 questionnaires in the Malay children with strabismus (p < 0.001). There was no significant difference between the psychosocial subscale mean scores of the two questionnaires in the children (p = 0.122). In the comparison between the Proxy IXTQ and AS-20, there was a significant difference noted in the total mean scores, the functional subscale and the psychosocial subscale mean scores between both questionnaires (p < 0.05). All the scores in AS-20 questionnaires are higher when compared to the scores from all IXTQ. Conclusion: The total mean score and functional subscale mean score were significantly lower in the Malay version of IXTQ compared to the Malay version of AS- 20 in the Malay children with strabismus. There was no significant difference in the psychosocial subscale mean score between the two questionnaires in the children. The total mean score, functional and psychosocial subscale mean score were significantly lower in the Malay version of IXTQ compared to the Malay version of AS-20 questionnaires in the parent of Malay children with strabismus.